2021
DOI: 10.1016/j.omtm.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lentiviral vector genome size and producer cell genomic to gag-pol mRNA ratios on packaging efficiency and titre

Abstract: Lentiviral vectors are showing success in the clinic, but producing enough vector to meet the growing demand is a major challenge. Furthermore, next-generation gene therapy vectors encode multiple genes resulting in larger genome sizes, which is reported to reduce titers. A packaging limit has not been defined. The aim of this work was to assess the impact of genome size on the production of lentiviral vectors with an emphasis on producer cell mRNA levels, packaging efficiency, and infectivity measures. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…S alone was most effective in generating a mixed population of iOPCs (see below). In agreement with previous studies [ 36 , 37 ], we observed a higher level of expression of smaller-sized constructs. However, an intermediate selection step performed in our protocol normalized these differences and allowed us to compare TF combinations irrespective of construct size.…”
Section: Discussionsupporting
confidence: 93%
“…S alone was most effective in generating a mixed population of iOPCs (see below). In agreement with previous studies [ 36 , 37 ], we observed a higher level of expression of smaller-sized constructs. However, an intermediate selection step performed in our protocol normalized these differences and allowed us to compare TF combinations irrespective of construct size.…”
Section: Discussionsupporting
confidence: 93%
“…A size reduction of 1 kb improved the transduction e ciency by more than 5-fold, which is consistent with previous work [21][22][23][24]. The two smallest CRISPR-Cas systems CjCas9 and RfxCas13d did yield the highest transduction titer, and the largest SpCas9 and AsCas12a systems exhibit the lowest titer.…”
Section: Production Is Not Affected By Increasing Size Of the Transge...supporting
confidence: 89%
“…Whereas the LV transduction e ciency on human and mouse stem cells dropped dramatically for viral RNAs that approached 6 kb, a modest reduction of their size of 0.6 kb rescued the transduction e ciency by more than threefold. Consistently, Sweeney et al showed that the LV titer drops with increasing genome size [24]. In general, genome sizes close to or exceeding that of the natural HIV template (9.8 kb) result in decreased packaging capacity and consequently a low transduction e ciency.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Large transgenes exceeding 10 kb have been reported [60,61]. However, the accommodation of large transgenes may come at the cost of lower functional viral titers, as previous studies showed a semi-logarithmic reduction of 3 to 4 folds in functional LV titer per kb increase in genome size [60,62]. Aside from these major advantages, LVs are negligibly inflammatory and induce only minute levels of phenotypic and functional DC maturation in vitro and in vivo [63] and our unpublished data.…”
Section: Advantages Of Lvs As Vaccine Vectorsmentioning
confidence: 61%